Metal‐Free Aminooxygenation of Alkynes: Efficient Synthesis of 3‐Aroylimidazo[1, 2‐a]‐N‐Heterocycles. Issue 7 (6th May 2016) - Reddy, K. Ranjith; Gupta, Ajai Prakash; Das, Parthasarathi
Abstract: An expeditious, one‐pot, N ‐iodosuccinimide‐promoted reaction has been developed for the synthesis of 3‐aroylimidazo[1, 2‐ a ]pyridines from 3‐phenylpropiolaldehyde and 2‐aminopyridines.This aminooxygenation process of alkynes is general and was successfully extended to access 3‐aroylimidazo[1, 2‐ a ]pyrazines and 3‐aroylimidazo[1, 2‐ b ]pyridazines. With the metal‐free conditions and great efficiency in expanding molecule diversity, this method is superior to the existing procedures in the synthesis of 3‐aroylimidazo[1, 2‐ a ]‐ N ‐heterocycles. Abstract : To the Nth power : An expeditious, one‐pot, N ‐iodosuccinimide (NIS)‐promoted reaction has been developed for the synthesis of 3‐aroylimidazo[1, 2‐ a ]pyridines from 3‐phenylpropiolaldehyde and 2‐aminopyridines.This aminooxygenation process of alkynes is general and was successfully extended to access 3‐aroylimidazo[1, 2‐ a ]pyrazines and 3‐aroylimidazo[1, 2‐ b ]pyridazines.